Semantiske relationer i en ny dansk begrebsordbog: genbrug på tværs af ordbøger - Nimb, Sanni (LexicoNordica, 2011)
This article discusses the synergies between thesauri, wordnets and semasiological dictionaries, describing how the lexical data from a wordnet (DanNet), as well as the data from a monolingual dictionary (The Danish Dictionary), are being used to establish a Danish thesaurus. In opposition to other thesauri, this one’s main organizing principle is the grouping of words by semantic criteria. It thus combines words from different parts of speech in different types of groups. Furthermore, a number of formalized data on the words’ semantic relations leave us with a large number of possibilities when it comes to using thesaurus information in the online presentation of The Danish Dictionary. It also means that the thesaurus can be used to extend the number of semantic relations in DanNet.